The multicomponent approach to N-methyl peptides: total synthesis of antibacterial (–)-viridic acid and analogues - Neves Filho, Ricardo A. W.; Stark, Sebastian; Westermann, Bernhard; Wessjohann, Ludger A. (Beilstein Journal of Organic Chemistry, 2012)
Two syntheses of natural viridic acid, an unusual triply N-methylated peptide with two anthranilate units, are presented. The first one is based on peptide-coupling strategies and affords the optically active natural product in 20% overall yield over six steps. A more economical approach with only four steps leads to the similarly active racemate by utilizing a Ugi four-component reaction (Ugi-4CR) as the key transformation. A small library of viridic acid analogues is readily available to provide first SAR insight. The biological activities of the natural product and its derivatives against the Gram-negative bacterium Aliivibrio fischeri were evaluated.
Keywords: antibiotic; anticancer; Gram negative bacteria; natural product; peptide coupling; peptides; peptoid; toxin; Ugi reaction